2021
DOI: 10.1002/pc.26412
|View full text |Cite
|
Sign up to set email alerts
|

Developing thermoplastic corn starch composites filled with brewer's spent grain for applications in biodegradable films

Abstract: Despite the growing interest in utilizing starch-based biodegradable films, their low mechanical properties generally limit them from being widely used. On the other hand, brewer's spent grain (BSG) is an abundant by-product thatdoes not yet have high added-value industrial use. This study proposes the development of starch-based composites filled with BSG for applications in biodegradable films. Different contents (1-5 wt%) of BSG fibers of different sizes (35, 60, and 100 mesh) were used aiming to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 64 publications
(112 reference statements)
0
16
0
Order By: Relevance
“…Castanho et al . (2022) produced thermoplastic starch films with MB and observed that the mechanical performance was improved when smaller fibres were used, with a higher surface area‐to‐volume ratio. Ferreira et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Castanho et al . (2022) produced thermoplastic starch films with MB and observed that the mechanical performance was improved when smaller fibres were used, with a higher surface area‐to‐volume ratio. Ferreira et al .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this sample also produced the highest expansion index and the greatest amount of pores in the structure, promising results when considering a commercial application of the materials. Castanho et al (2022) produced thermoplastic starch films with MB and observed that the mechanical performance was improved when smaller fibres were used, with a higher surface area-to-volume ratio. Ferreira et al (2019) observed that expanded trays based on starch and MB had a higher rigidity than the expanded polystyrene, which is consistent with the results of this work.…”
Section: Hardness and Brittleness Of The Materialsmentioning
confidence: 99%
“…cellulose, and 35%(wt.) hemicellulose (Ferreira et al ., 2019; Castanho et al ., 2022). Animal and human nutrition are the current applications of BSG, which includes solid fuel, as fillers for reinforcing materials, and as fertilisers.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic starch (TPS) materials have been considered as fully renewable packaging materials for pharmacy, food, and cosmetic, because they own good meltprocessibility and/or oxygen barrier properties. [30][31][32][33][34] Relatively small OTR of $80, $105, and $120 cm 3 /m 2 ÁdayÁatm at $25 C/50% RH were acquired for corn ($150 μm), potato ($35 μm), and tapioca starch films ($80 μm), respectively. [31][32][33] While the OTR at 25 C/50% RH for plasticized tapioca films ($50 μm) increased from $90 to $100 cm 3 /m 2 ÁdayÁatm, when glycerol loadings increased by 5 wt%.…”
Section: Introductionmentioning
confidence: 99%